2010
DOI: 10.5194/gh-65-36-2010
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of child health inequalities in the province of Punjab, Pakistan : the advantages of GIS in data analysis

Abstract: Abstract. In the overall context of the Millennium Development Goals, Pakistan recently embarked on an effort to collect data regarding crucial issues of human development, such as health, poverty, and education. For their effective use in policy formulation, however, governments need to find ways of making the data easily accessible. It is argued that Geographical Information Systems (GIS) can play a major role here. The data compiled by the Federal Bureau of Statistics at district level are used in this arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Similarly, Shams [40] highlighted health poverty in the light of four very important socio-economic (gender, education, income and age) dimensions. On the other hand, Rehman and Zimmer [41] described child health status by utilizing maternal literacy, poverty, vaccination, level of nutrition & water and Sanitation as key dimensions. Ahmed and Mustafa [42] found that people living in slums face severe health problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Shams [40] highlighted health poverty in the light of four very important socio-economic (gender, education, income and age) dimensions. On the other hand, Rehman and Zimmer [41] described child health status by utilizing maternal literacy, poverty, vaccination, level of nutrition & water and Sanitation as key dimensions. Ahmed and Mustafa [42] found that people living in slums face severe health problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Shams [40] highlighted health poverty in the light of four very important socio-economic (gender, education, income and age) dimensions. On the other hand, Rehman and Zimmer [41] described child health status by utilizing maternal literacy, poverty, vaccination, level of nutrition & water and Sanitation as key dimensions. Ahmed and Mustafa [42] found that people living in slums face severe health problems.…”
Section: Literature Reviewmentioning
confidence: 99%